Pengenalan Bahasa Inggris kepada Anak Usia Dini - Sa’dulloh Muzammil (Raheema, 2019)
Kids may be exposed to English as an international language at very early age, particularly at golden age. It is a critical period in which kids can amazingly absorb languages by hearing words from their surroundings especially those they hear from their family members. Yet, parents should be aware of joyful strategies to introduce English for their kids. Parents can introduce simple words and phrases to kids and may not force them to understand grammar. Playing games and singing songs may become strategies to make kids familiar with English.